(untitled) (XXI Century. Spanish Literature and Culture, 2005)
Essay that studies the situation of the current novel that is suffering from withdrawal, or finishing of art. Reflect on the changes that postmodernity and art contemporary have made on the way of conceiving art in general and on the novel in particular.